The effects of Covid-19 on the regulatory key performance indicators in the European banking sector: an empirical analysis of the short-term effects in the aftermath of the Covid-19 outbreak - Klimpel, Benjamin Johannes (2021)
The paper scrutinizes the impact of the Covid-19 pandemic and the induced containment measures on the banking system in the euro-zone. As the first line of defense mechanism against credit losses, profits are essential for a vital banking sector. As a measure of profitability, the return-on-equity (RoE) has been considered. The paper investigates potential drivers for the RoE development and evaluates the effect of Covid-19 on the RoE using supervisory data published by the European Central Bank on a quarterly basis. In this analysis, a dummy representing the outbreak of Covid-19 in the European Union in 2020-Q1 has been introduced. Using this approach, a statistically significant drop in the RoE of the banking sector of approximately6 percentage-points could be perceived.